Prolonged Hypoglycemic Encephalopathy: A Case Report - Newton Ashish Shah; Santosh Bastola; Abhishek Kumar Shah; Manish Yadav (Clinical Case Reports, 2024)
ABSTRACT Hypoglycemic encephalopathy is a rare yet life‐threatening diabetes complication, where overlapping symptoms with neurological conditions can delay diagnosis. Early recognition and treatment are crucial to prevent irreversible brain damage. Clinicians should suspect hypoglycemia in diabetic patients with altered mental status, as timely intervention improves outcomes and reduces mortality.